How we manage patients with heparin induced thrombocytopenia. (21st April 2016) - Scully, Marie; Gates, Carolyn; Neave, Lucy
Summary: Heparin induced thrombocytopenia (HIT) remains a rare, but significant, condition related to mortality and morbidity. The incidence has decreased with reduced use of unfractionated heparin, with the exception of cardiac surgery. Due to the high risk of thrombosis, a switch to a non‐heparin anticoagulant is required, until platelet counts normalize. Within the acute setting, argatroban, fondaparinux and direct acting oral anticoagulants (DOACS) are therapeutic options. In patients with HIT‐associated thrombosis or who require long‐term anticoagulation, warfarin remains the preference, but DOACs are attractive alternatives.